Importance of eosinophilic infiltration of the colonic mucosa in ulcerative colitis patients who are refractory to maintenance therapy: A prospective, single-center study. Issue 40 (7th October 2022) - Miyazu, Takahiro; Ishida, Natsuki; Asai, Yusuke; Tamura, Satoshi; Tani, Shinya; Yamade, Mihoko; Hamaya, Yasushi; Iwaizumi, Moriya; Osawa, Satoshi; Furuta, Takahisa; Baba, Satoshi; Sugimoto, Ken
Abstract : Eosinophilic infiltration is sometimes observed histologically in ulcerative colitis (UC), but the effect of the degree of infiltration on the treatment course for UC is not completely understood. We investigated whether short-term steroid administration in UC patients refractory to maintenance therapy, with high eosinophilic infiltration in the colonic mucosa, contributed to the clinical and endoscopic improvement. Ten patients with endoscopically active and pathologically high eosinophilic infiltration, based on pathological examination using endoscopic biopsy, were examined for the clinical background when starting steroid treatment. The clinical and endoscopic improvement before and after steroid use were assessed prospectively. The average initial steroid dosage and duration of use were 21.0 mg and 102.7 days, respectively. The mean values before and after steroid use of the clinical activity index, the Mayo endoscopic subscore, and the UC endoscopic index of severity were 2.4 and 1.0, 1.8 and 0.7, and 3.9 and 1.1, respectively. All scores improved significantly after steroid use ( P = .042, P = .002, P = .002, respectively). Steroids were discontinued in all patients; no patients required steroid re-administration. There may be cases of UC with eosinophilic infiltration into the colonic mucosa and resistance to maintenance treatment, suggesting that short-term steroid administration may contribute to clinical and endoscopic improvements.